International business, multi-nationals, and the nationality of the company - Gehlen, Boris 1973-; Marx, Christian 1977-; Reckendrees, Alfred 1962- (Routledge, Taylor and Francis Group, 2024)
This book discusses challenges that arise for multinational companies from not having a single 'nationality' and being exposed to a variety of simultaneous country-specific, legally, and culturally constructed nationalities at home and abroad. Brexit, America First campaigns, Russia's war against Ukraine, or the ever-tenser relationship between China and the US have led to raising concerns about foreign direct investments. Multinational companies are pressured to withdraw from countries and reorganise global value chains. The long-held confidence that 'nationality' does not matter for multinational companies in the globalised economy has dwindled. Today, companies doing business abroad are exposed to implications of their 'nationality' because governments and customers react upon the 'nationality' of a firm or a product as they did in the 20th century.The chapters in this book address many international business domains, covering political risk, liability of foreignness, cultural distance, headquarters change, and tax planning. They use different methodological approaches to analyse European and US-based MNEs in Europe, Africa, and South-East Asia from 1900 to 1980. The book argues that 'nationality' is not a ghost from the past in international business, it is a topic that requires substantial consideration.The chapters in this book were originally published in the journal Business History
Keywords: Aufsatzsammlung